Videojuego dota 2 y sus cambios en los patrones socioculturales de los doteros de un lan center de Iquitos 2022 - Toscano Vásquez, Harol Flavio (2023)
This thesis entitled: Dota 2 Video Game and its Changes in the Sociocultural Patterns of the Doteros of a LAN Center in Iquitos 2022, was carried out at the LAN Center CNC Digital of the district of Iquitos, alias Chesternet (old name). Whose objective is the description of the changes that the ludification of the Dota 2 video game originates in the sociocultural patterns of its players (doteros) of the LAN Center CNC Digital de Iquitos. A deconstructive quasi-experimental qualitative method was used, in order to critically and reflexively approach the Game studies (Ludology) from anthropology. It is highlighted that the deconstructive ethnographic methodology allowed to holistically understand how the doteros experience, they build and attribute meanings to their reality in the context of video games. Concluding that there is a culture of video games in Iquitos, and therefore in the Loreto region, represented by Chester's doteros. Therefore, for social anthropology, the results offer a critical and holistic vision of these playful phenomena, helping to enrich our understanding of the interaction between the world of video games and local culture, underlining the importance of recognizing and valuing the cultural expressions of postmodernity.